Effect of enzymatic interesterification on melting point of palm olein - Yassin, Atif A. A.; Mohamed, Ibrahim O.; Ibrahim, Mohd N.; Yusoff, Mohd S. A. (2003)
Immobilized PS-C 'Amano' II lipase was used to catalyze the interesterification of palm olein (POo) with 30, 50, and 70% stearic acid in n-hexane at 60°C. The catalytic performance of the immobilized lipase was evaluated by determining the composition change of fatty acyl groups and triacylglycerol (TAG) by gas liquid chromatography and high-performance liquid chromatography, respectively. The interesterification process resulted in the formation of new TAGs, mainly tripalmitin and dipalmitostearin, both of which were absent in the original oil. These changes in TAG composition resulted in an increase in slip melting point, from the original 25.5°C to 36.3, 37.0, and 40.0°C in the modified POo with 30, 50, and 70% stearic acid, respectively. All the reactions attained steady state in about 6 h. This type of work will find great applications in food industries, such as confectionery.